Psalm 67: harvest thanksgiving psalm, (eschatological) hymn, communal prayer, communal lament or ...? - Prinsloo, Willem Sterrenberg (Old Testament essays, 1994)
One of the most perplexing questions posed by Psalm 67 has been how to determine the mood and tense of its verbs. This choice has often played a decisive role in determining the psalm's Gattung. The Gunkelian idea of how a Gattung should be regarded also seems to have been significant in shaping these choices. The research is also characterised by a lack of agreement on the structure and strophic segmentation of the psalm. There are some who detect a perfect chiastic structure in the psalm and those who would disagree. A text-immanent analysis, emphasising morphological, syntactical, stylistic and semantic aspects, can open discussion on these points and other questions of interpretation in an attempt to provide solutions for these problems, as far as is possible within such a text-immanent approach.